The effect of PQ4R strategy on the achievement of second-grade students average in reading and text material - Al-Jubouri , Asma Salam Kahlil (International Journal of Psychosocial Rehabilitation, 2020)
This research is determined by a sample of the second middle-class students in the martyr Qasim Tarish School in the Ali Sharqi district of Maysan Governorate, and the topics of the reading book and the texts to be taught to middle second-grade students in Iraq for the second semester of the 2017-2018 academic year.The researcher adopted the experimental method with partial control, to suit it with the nature of the research. The research sample consisted of (60) middle-grade students, and they were randomly selected from the middle of the martyr Qasim Tarish in the Ali Sharqi district of the Maysan Governorate for the academic year 2017-2018, and this sample was divided randomly by two groups, one of them (one). The reading and the texts are strategic (PQ4R) and it was the share of Division (B), and the control group consisted of (30), they studied in traditionally, and they were from the share of Division (A). The following changes (the age, calculated by months, and the Arabic language scores for the previous academic year, and by using a square (such as) in the academic achievement variables for parents and mothers After the researcher identified the subjects of reading material and the texts that will be studied during the duration of the experiment represented by the second course, the researcher formulated the behavioral goals, prepared the teaching plans for them, presented them to a group of experts and specialists to judge their validity, then made the necessary adjustments and became ready plans for application in the light of their opinions to measure the achievement of students of the two research groups in the topics studied by the researcher himself, I prepared an achievement test consisting of (20) objective test items of the type (multiple choice), and the researcher confirmed the validity of the test, calculating its stability, and from the discriminatory forces and factors of paragraph difficulty.After the end of the experiment that started on 19/19/2018 and ended on 4/30/2018, the researcher applied the achievement test to the students of the experimental and control research groups, and after analyzing the results of the students’ answers and statistically treating them using the T-test for two independent samples (t-test) to find out the significance of the difference At the level of (0.05) between the two research groups, it is clear that:The presence of a statistically significant difference at the level of significance (0.05) between the average score of the second-grade students average who are studying according to the strategy of Toms and Robinson PQ4R)) and the average score of the average second-grade students who studied according to the usual method of achievement and the result was in favor of the experimental group.The researcher recommended adopting a strategy (PQ4R) in teaching reading and texts for the second intermediate grade, and caring for teaching reading material for neglect and making time for her class to teach the rules or rest. The researcher suggested conducting a study similar to the current study in other study stages such as junior high, and conducting a similar study in Reading and text material aims to identify the impact of using the PQ4R strategy in creative thinking, critical thinking, acquisition of concepts, and direction towards the material.